2022
DOI: 10.22541/au.166965409.98209704/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Design of Miniature Planar Antennas for 5G Systems

Abstract: The objective of this work is the design and simulation of an antenna based on metamaterials in order to miniaturize the dimensions of planar antennas. Metamaterials have been on the rise in recent years. The new properties make it possible to envisage the realization of new electronic components with new functions. Metamaterials are artificial materials designed for different telecommunications applications in order to improve the performance of antennas in terms of efficiency, compactness and miniaturization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The use of potassium is a spray on the plant because it is an additional factor for transferring carbohydrates from the leaves to the roots; in addition to the role of this element in regulating the process of opening and closing stomata in the leaves, which increases the process of photosynthesis and the ability of metabolism, as well as increasing the activity of many enzymes that regulate activities. Research conducted by [17] showed that spraying the chrysanthemum plant Calendula officinalis L. shoots with seaweed extract at a concentration of 1 ml. Liter¹ caused a significant increase in plant height, number of branches, number of leaves, total leaf area, and wet weight of leaves.…”
Section: Total Alkaloids Content %mentioning
confidence: 99%
“…The use of potassium is a spray on the plant because it is an additional factor for transferring carbohydrates from the leaves to the roots; in addition to the role of this element in regulating the process of opening and closing stomata in the leaves, which increases the process of photosynthesis and the ability of metabolism, as well as increasing the activity of many enzymes that regulate activities. Research conducted by [17] showed that spraying the chrysanthemum plant Calendula officinalis L. shoots with seaweed extract at a concentration of 1 ml. Liter¹ caused a significant increase in plant height, number of branches, number of leaves, total leaf area, and wet weight of leaves.…”
Section: Total Alkaloids Content %mentioning
confidence: 99%